Study of effect of anthelmintic treatment on metabolic profile of anestrus Haryana cows - SINGH, C P; SAXENA, ATUL (The Indian Journal of Animal Reproduction, 2023)
Thirty four Haryana cows were selected (24-anestrus and IO-normal cyclic) from the university farm for the study of metabolic profile of anestrus cows in response to anthelmintic treatment. Faecal samples of these animals were examined for the presence of parasitic eggs. Haematobiochemical studies viz. haemoglobin (Hb ), glucose and total protein were also conducted. An overall increase ofHb, serum glucose and total protein concentration in anthelmintic treated animals was greater than untreated group. This might be because of increased feed consumption by anthelmintic treated animals. The concentration of Hb was significantly higher (P<0.0 1) in cyclic cattle compared to anthelmintic treated and untreated an estrus animals. The concentration of glucose in cyclic animals was also higher compared to both, anthelmintic treated and untreated groups but the difference being non-significant. The total protein concentration in cyclic animals was lower significantly (P<0.05) compared to anthelmintic treated and non-significantly compared to anthelmintic untreated animals showing that the concentration of total protein is not related with the exhibition of estrus symptoms. Four (23.53%) animals came into estrus after treatment with fenbendazole whereas in untreated group, only one (14.29%) animal came into estrus. This shows that anth .. lniintic treatment is useful in relation to exhibition of estrus.